Vegetation and Animal Production in Pastures Sprayed for Western Ragweed Control - Keith Harmoney; John Jaeger (Kansas Agricultural Experiment Station Research Reports, 2022)
Western ragweed (Ambrosia psilostachya) is a common native forb found throughout Kansas native rangelands and in some seeded pastures. Over time, western ragweed can form dense colonies from growth of lateral creeping rootstalks with multiple buds that can initiate new growth and form an upright stem and plant. Past research has shown that western ragweed does not compete with native grass production until ragweed contributes over approximately 35% of the forage dry matter of a pasture area. Cattle have utilized western ragweed in past long-term historical grazing trials. In a previous long-term trial at Hays, KS, western ragweed was the most common forb found in light and moderately stocked pastures. Frequency of western ragweed was greatest in pastures with light stocking rates, and frequency of western ragweed declined by nearly 50% in moderately stocked pastures because animals utilized the western ragweed. In heavy stocking rate pastures, western ragweed was found in only trace amounts because of greater animal use. However, producers still question if cattle utilize western ragweed and achieve adequate gains in pastures with high western ragweed populations. Therefore, we conducted a grazing trial to determine if controlling western ragweed in pasture improved stocker animal gains compared to pastures with no ragweed control.
Keywords: body weight gain; dicamba; dry matter composition; native forb; proportion; stocker animals